Simulasi Filter Aktif pada 6 Pulse STATCOM Untuk Mereduksi Total Harmonic Distortion (THD) Di Sistem Transmisi Bali - Nugraha, Made Dika; Manuaba, Ida Bagus Gede Ida Bagus Gede; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 18 No 2 (2019): (Mei-Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i02.P06, 2019)
The emergence of harmonics caused by electrical loads that are not linear. Input of harmonic current can cause sinusoidal. Content that exceeds the limit can cause poor power quality. The level of harmonic distortion or called Total Harmonic Distortion (THD) on the network causes losses and voltage drops, which affects the efficiency of the transmission network system. Harmonic attenuation is the right choice to reduce harmonic current (THDi). Based on the IEEE 519-1992 standard the expected harmonic current must be below 5%. In this study an active filter has been designed to be able to drain the harmonic current contained in the system using the 6 pulse converter on Statcom.